Analisa Perceived Ease Of Use Dan Perceived Enjoyment Terhadap Behavior Intention Pada Digital Payment ( Studi Kasus Mahasiswa Universitas Islam Malang 2019 ) - Febbyola, Risa; Mardani, Ronny Malavia; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the Analysis of Perceived Ease Of Use and Perceived Enjoyment of Behavior Intention in Digital Payment (Case Study of Islamic University of Malang Students 2019). The type of approach taken is a quantitative approach. With the type of explanatory research. The sample used in this study was 96 respondents obtained from the calculation of the Slovin formula using a questionnaire. The data analysis method used in this study is multiple linear regression analysis. The data testing used is partial hypothesis testing (Test t). In the results of his research, it was shown that perceived ease of use does not affect behavior intention in the use of digital payments, while perceived enjoyment affects behavior intention in the use of digital payments. Keywords : Perceived Ease Of Use, Perceived Enjoyment, Behavior Intention, Digital Payment